2004
DOI: 10.1002/anie.200460516
|View full text |Cite
|
Sign up to set email alerts
|

Helix inside a Helix: Encapsulation of Hydrogen‐Bonded Water Molecules in a Staircase Coordination Polymer

Abstract: A stream of water molecules, held together by hydrogen bonding, forms a left‐handed helix within the helical channels of a left‐handed staircaselike metal coordination polymer. The result is a novel helix‐in‐a‐helix structure. The water‐filled channel can be seen on viewing the coordination polymer along the b axis (see picture; C gray, N blue, Ni green, O red).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
71
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(72 citation statements)
references
References 47 publications
1
71
0
Order By: Relevance
“…Recently, significant progress has been made with respect to characterization of 1-D water chains and tapes [12][13][14][15][16][17][18]. These studies have significantly advanced our understanding of the behavior of bulk water [5,[12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, significant progress has been made with respect to characterization of 1-D water chains and tapes [12][13][14][15][16][17][18]. These studies have significantly advanced our understanding of the behavior of bulk water [5,[12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, significant progress has been made with respect to characterization of 1-D water chains and tapes [12][13][14][15][16][17][18]. These studies have significantly advanced our understanding of the behavior of bulk water [5,[12][13][14][15][16][17][18]. But very little is known about how these clusters link themselves within the lattice of a crystal host to form larger networks of water molecules, so that there are very few examples of 2-D [4,[19][20][21][22][23][24] or 3-D [25][26][27] water polymers.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Further, in our recent report, we showed that incorporation of an additional carboxylate group in the side arm of the ligand N-(2-hydroxybenzyl)--glutamic acid formed between salicylaldehyde and -glutamic acid resulted in a novel structural display of a spiral staircase conformation. [5] Copper() complexes of the reduced Schiff-base ligand derived from salicylaldehyde and histidine have been found to self-assemble to form a capsule incorporating four pyridine molecules. [6] Various dicopper active sites found in copper-containing metalloenzymes have similar structural aspects with three histidine donors for each of the two Cu centers, which are separated by a distance of about 3.5 Å, and catechol oxidase as one of the prominent members of the type III copper proteins that catalyze the two-electron oxidation of ortho-diphenols to the corresponding quinones.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22] Chakravarty described an unprecedented 1D helical chain of water in a dicopper(ii) complex with a helical porous supramolecular structure- [20] and Vittal reported a staircase-like helical coordination polymeric architecture of a nickel(ii) complex that hosts a 1D helical chain of lattice water molecules in a helical pore. [21] In these two cases, the 1D helical water chains are anchored by helical host complexes through weak hydrogen-bonding interactions and exhibit an alternate arrangement of two water molecules in the chains. While trying to construct chiral porous materials using a simple Schiff-base ligand derived from l-histidine, we obtained complex [Cu 2 (l-shis) 2 ]·4H 2 O (1) (H 2 shis = Nsalicylidenylhistidine), in which lattice water molecules are well ordered and arrayed in an AABB fashion to form 1D left-handed helical water chains encapsulated in the channels of the H-bonded supramolecular complex.…”
Section: Introductionmentioning
confidence: 99%